EFFECT OF MIXED FEEDING SCHEDULE ON GROWTH AND NUTRIENT UTILISATION IN ROHU, LABEO ROHITA (HAM.) FINGERLINGS - SAMAL, J. K.; MOHANTY, S. N. (Journal of Indian Fisheries Association, 2015)
Studies on nutrient utilisation and growth of rohu (Labeo rohita) fingerlings (3.13-4.09 g) raised on seven feeding schedules under laboratory conditions (26.3-33.5Â°C) showed that two days regular feeding on Diet B (high protein, 38.90%) resulted in maximum growth and protein retention efficiency. While regular feeding on low protein diet (Diet .A) resulted in poor nutrient utilisation and growth of fish, high protein diet (Diet B) did not show any significant difference in growth from the mixed 2A-3B schedules but exhibited comparatively low protein retention efficiency. The other feeding schedules were 1A-2B, 1A-3B, 2A-2B AND 2A-4B, where the numerical value refers to the number of days for continuous feeding of a particular diet. The diets A and B served as the controls which contained 3.40 and 3.67 kcallg gross energy respectively. The 2A-3B feeding schedule was also found to be highly economic as an expenditure of Rs.ll/- only was required for raising the body weight by one kilo as against Rs.17/- with high protein diet (Diet B) as calculated.